City Energy Efficiency Assessments - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2015)
For cities that want to take concrete actions on improving energy efficiency, it is essential to understand what, where, and how big the potential energy-saving opportunities are, what measures are needed to capture the savings and at what costs, what the implementation constraints are, and how priorities should be set given local capacity and resources. An energy efficiency assessment can provide the necessary clarity on these issues. Energy efficiency assessments can be done at different depths and with varying scopes, depending on the city's needs, capacity, and resources. The duration and cost of the assessment depends on the quality of existing data and the size and complexity of the sector. This guidance note provides an introduction to the objectives, scope, and outputs, as well as the basic steps and approaches of conducting the three types of energy efficiency assessments.